Pengembangan Media Pembelajaran Bulu Tangkis Berbasis Canva elalui Video Animasi di Sekolah Menengah Atas - Rahman, Muhammad Taufik; Usra, Meirizal; Yusfi, Herri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to determine the feasibility and practicality of the learning media being developed. This type of research is research and development (R&D). The development procedure includes needs analysis, design, development, implementation, and evaluation. The material expert validation results were 87% with a very valid category. The validation results from media experts were 89% with a very valid category. The test results for small-group students were 89.16% in the convenient category. The test results for the large group of students were 95.04% in the convenient category. The effectiveness test saw an increase in learning outcomes from 67.11% to 87.33%, which means that after using animated video learning media based on the Canva application, there was an increase of 20.22% in the very effective category. Animated video learning media based on the Canva application is proven by increasing student learning outcomes based on pretest and posttest evaluation data. In conclusion, the animated video learning media based on the Canva application in high school is said to be very valid, as seen from the research results by getting a percentage of 87.27% of material validators in the valid category and 89% of media validators in the very valid category. Keywords: Development, Animation Video, Canva Application